An approach to rank picture fuzzy numbers for decision making problems - Si, Amalendu; Das, Sujit; Kar, Samarjit (Decision Making: Applications in Management and Engineering, 2019)
Comparison of picture fuzzy numbers (PFNs) are performed using score and accuracy values. But when both of the score and accuracy values are equal, those PFNs are said to be identical. This article presents a novel method to compare the PFNs even when the score and accuracy values of those PFNs are equal. The proposed ranking method is based on positive ideal solution, positive and negative goal differences, and score and accuracy degrees of the picture fuzzy numbers. A new score function is proposed to calculate the actual score value which depends on the positive and negative goal differences and the neutral degree. Finally, a real-life example has been used to illustrate the efficiency of the proposed method.